Relevance of Heart Failure in Prevention, Treatment and Prognosis of Ischemic Stroke - Haeusler, Karl Georg; Endres, Matthias; Doehner, Wolfram (Neurology International Open, 2017)
About 1.2 million people in Germany suffer from heart failure (HF) and HF is present in about 13–29% of all patients with acute ischemic stroke. HF is a risk factor for ischemic stroke and it is accompanied by a comparably high morbidity and mortality after stroke. Only limited data are available regarding the relevance of HF in acute ischemic stroke. The hypothesis has emerged that an acute ischemic stroke may contribute to deterioration and occurrence of heart failure. Stroke prevention by oral anticoagulation is only recommended for HF patients with concomitant atrial fibrillation. This article is based on a selective literature review summarizing the present knowledge as well as current guideline recommendations and provides recommendations for clinical practice.
Keywords: heart failure; ischemic stroke; stroke prevention; oral anticoagulation